Exosomes secreted from GATA-4 overexpressing mesenchymal stem cells serve as a reservoir of anti-apoptotic microRNAs for cardioprotection. (1st March 2015) - Yu, Bin; Kim, Ha Won; Gong, Min; Wang, Jingcai; Millard, Ronald W.; Wang, Yigang; Ashraf, Muhammad; Xu, Meifeng
Abstract: Background: Exosomes play an important role in intercellular signaling and exert regulatory function by carrying bioactive molecules. This study investigated (1) the cardioprotective capabilities of exosomes derived from mesenchymal stem cells (MSCs) overexpressing GATA-4 (MSC GATA-4 ) and (2) its underlying regulatory mechanisms for expression of target proteins in recipient cells. Methods and results: Exosomes were isolated and purified from MSC GATA-4 (Exo GATA-4 ) and control MSCs (Exo Null ). Cell injury was investigated in primary cultured rat neonatal cardiomyocytes (CM) and in the rat heart. Exosomes contributed to increased CM survival, reduced CM apoptosis, and preserved mitochondrial membrane potential in CM cultured under a hypoxic environment. Direct intramyocardial transplantation of exosomes at the border of an ischemic region following ligation of the left anterior descending coronary artery significantly restored cardiac contractile function and reduced infarct size. Real-time PCR revealed that several anti-apoptotic miRs were highly expressed in Exo GATA-4 . Rapid internalization of Exo GATA-4 by CM was documented using time-lapse imaging. Subsequent expression of these miRs, particularly miR-19a was higher in CM and in the myocardium treated with Exo GATA-4 compared to those treated with Exo Null . The enhanced protective effects observed in CM were diminished by the inhibition of miR-19a. The expression level of PTEN, a predicted target of miR-19a, was reduced in CM treated with Exo GATA-4, which resulted in the activation of the Akt and ERK signaling pathways. Conclusions: Exo GATA-4 upon transplantation in the damaged tissue mediate protection by releasing multiple miRs responsible for activation of the cell survival signaling pathway. Highlights: This study highlights the importance of MSC overexpressing GATA-4 derived exosomes (Exo GATA-4 ) in cardiac protection. Exo GATA-4 release anti-apoptotic miRs, which result in a regulation of various cell survival signaling pathways. Exosomes are potential candidates for adjunctive therapy for acute myocardial infarction.